Advancing into Water's "No Man's Land": Two Liquid States?. Issue 44 (22nd September 2014) - Paschek, Dietmar; Ludwig, Ralf
<x xml:space="preserve">Abstract</x> A tale of two liquids? Liquid water exhibits many anomalous properties which are strongly amplified in the supercooled state. A possible explanation for the unusual behavior is a phase transition between two distinct metastable forms of liquid water at deeply supercooled conditions. A recent theoretical study has confirmed the existence of this liquid–liquid phase transition.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>